Economic gangsters : corruption, violence, and the poverty of nations - Fisman, Raymond; Miguel, Edward (Princeton : Princeton University Press, 2008)
This book is a fascinating exploration of the dark side of economic development.
Fighting for economic development -- Suharto, Inc. -- The smuggling gap -- Nature or nurture? understanding the culture of corruption -- No water, no peace -- Death by a thousand small cuts -- The road back from war -- Learning to fight economic gangsters -- Epilogue : doing better this time.
Includes bibliographical references (p. [215]-233) and index.
aug 27/05/13
Loans
Keywords: Corruption -- Economic aspects; Political corruption -- Economic aspects; Smuggling